2013
DOI: 10.1159/000353561
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Surgically Treated Primary Spinal Cord Tumors in Miyagi, Japan

Abstract: Background: Data for spinal cord tumors have not been collected in the past on a population-based level in Japan. The objective of the study was to provide detailed estimates of the population-based incidence of surgically treated primary spinal cord tumors in Japan. Methods: Incidence of primary spinal cord tumors was estimated from patients treated surgically between 2008 and 2010 in Miyagi Prefecture. The overall incidence of spinal cord tumors was calculated, as well as the individual incidence rates accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Of note, the overall incidence of spinal schwannomas appears to be greater in Japan than in Western countries. 18,19 Similarly to other surgical series, in our study the lumbar spine was the most common segment in which conventional schwannomas were found. In addition, the majority of our patients' tumors were intradural-extramedullary which is consistent with all other comparable surgical series.…”
Section: Discussionsupporting
confidence: 82%
“…Of note, the overall incidence of spinal schwannomas appears to be greater in Japan than in Western countries. 18,19 Similarly to other surgical series, in our study the lumbar spine was the most common segment in which conventional schwannomas were found. In addition, the majority of our patients' tumors were intradural-extramedullary which is consistent with all other comparable surgical series.…”
Section: Discussionsupporting
confidence: 82%
“…8 The incidence of SCHs was reported to be approximately 4-5 times the incidence of meningiomas in Japan. 3,6 In the present study, we suspected that 23 of 24 radiologically observed, solitary, intradural extramedullary tumors were SCHs. The majority of the affected cord levels were in the lumbar region, similar to another report.…”
Section: Discussionmentioning
confidence: 58%
“…Among other case series that included patients with primary spinal cord tumors, both intramedullary and extramedullary, the most frequent histological type in Asian studies was schwannoma. This proportion seems to be especially increased in the Japanese population, where schwannomas account for 56% and 57.2% of the lesions [ 7 , 19 ]. This trend seems to be repeated in the Latin American population, being the most frequent histological type in a Mexican series [ 10 ] and in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological indicators, such as the incidence and prevalence of these lesions, seem to vary in geographically and ethnically different populations [ 6 ], and most studies have been conducted in the USA, Europe, and Asia [ 7 ]. There are few articles regarding the epidemiology of these lesions in Latin American populations.…”
Section: Introductionmentioning
confidence: 99%